2022
DOI: 10.1111/ijcs.12813
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of halal food scholarly publications: A PubMed bibliometric network analysis

Abstract: Halal food research has witnessed a distinct proliferation during the past decade. In this article, we examine the intellectual structure of the field based on 302 PubMed documents written by 686 authors representing 45 nations and spanning 30 years . The study applies bibliometric network techniques to explore the halal food impactful authors, influential journals, collaboration networks and emerging trends. Social network analysis (SNA) techniques are also used to unearth and mine the intellectual structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…During the past ten years, Halal food research has seen a noticeable increase [ 3 ]. As Muslim communities grow, so too does the demand for products and services that comply with Halal standards [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…During the past ten years, Halal food research has seen a noticeable increase [ 3 ]. As Muslim communities grow, so too does the demand for products and services that comply with Halal standards [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study has significant theoretical and practical ramifications for those involved in the Indonesian Halal food business. Mostafa [ 3 ] showed that the network of collaboration in the field of Halal cuisine is thin. According to Al-Shami and Abdullah [ 24 ], the Halal food business faces several difficulties in its management, promotion, and certification procedures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations